Estimation of coordinating abilities of a person based on analysis of electromiographic patterns of movements - N. S. Davydova; I. Yu. Mihuta; A. N. Osipov; A. A. Boriskevich; V. E. Vasyuk; A. A. Hoholko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The effective approach to the estimation of athletes coordination abilities based on the reproducibility analysis of the electromyographic patterns of motion tests under the influence of external destabilizing factors is proposed. The following factors are chosen as external perturbing ones: disabling the visual and disabling the sound analyzer of a person. Two coefficients for the quantitative estimation of influence of the visual and sound analyzer on the stability of reproduction of movements with a complex coordination structure are introduced. The recommendations on the practical use of the research results for young athletes are given.